Kekuatan Hukum Surat Kuasa dari Luar Negeri yang Tidak Dilegalisasi oleh Kedutaan Besar Indonesia - Zaenul Abidin; Jordan Alexander Wirasasmita (Mahesa Research Center, 2022)
This article aims to find out how the provisions for the legalization of power of attorney from abroad at the Embassy of the Republic of Indonesia, as well as the enactment of Presidential Regulation Number 2 of 2021 concerning Ratification of the Convention on the Elimination of Legalization Requirements for Foreign Public Documents. This research method is normative legal research, using legal rules, legal principles, and legal doctrines in statutory regulations. This study concludes that the power of attorney agreement is regulated in Article 1792 of the Civil Code, granting power of attorney is an agreement by which one person gives his power to another person who accepts it for and on his behalf to carry out an affair. As stated in Article 2 of the Minister of Foreign Affairs 13/2019, power of attorney originating from abroad must go through legalization steps, but if it refers to PP 2/2021, this is actually no longer necessary, as in Article 4 apostille convention stipulates regarding certification or apostille which basically has the same purpose as legalization as regulated in Minister of Foreign Affairs Regulation 13/2019.